Gastrocolic Fistula: A Shortcut through the Gut - Nauzer Forbes; Raed Al-Dabbagh; Peter Lovrics; David Morgan (Canadian Journal of Gastroenterology and Hepatology)
Gastrocolic fistulas are observed in association with several conditions. Traditionally, peptic ulcer disease was commonly implicated in the formation of gastrocolic fistulas; however, this is now a rare etiology. Here, we present a case of gastrocolic fistula secondary to peptic ulcer disease alone, in addition to reviewing the literature and providing options for diagnosis and treatment.